2020
DOI: 10.1039/d0sc03391j
|View full text |Cite
|
Sign up to set email alerts
|

A rationally designed peptoid for the selective chelation of Zn2+ over Cu2+

Abstract: The selective removal of Zn2+ from proteins by a synthetic chelator is one of the promising therapeutic approaches for the treatment of various diseases including cancer. Although the chelation of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…152 A set of peptoid trimers with two copper(II) chelating units, as well as non-coordinating peptoid monomer, was designed by Mayaan et al By varying the nature and position of the noncoordinating unit, they found selective binders for Cu 2+ that were even able to remove the ions from the natural copperbinding protein metallothionein. 153 The working group also applied their peptoid design to build potent ruthenium(II), 154 cobalt(II) 155 , and zinc(II) 156 chelators (Table 2). The Kirshenbaum working group identified peptoid-based nickel(II) chelators with the help of bench-top X-ray fluorescence (XRF, Table 2).…”
Section: Figurementioning
confidence: 99%
“…152 A set of peptoid trimers with two copper(II) chelating units, as well as non-coordinating peptoid monomer, was designed by Mayaan et al By varying the nature and position of the noncoordinating unit, they found selective binders for Cu 2+ that were even able to remove the ions from the natural copperbinding protein metallothionein. 153 The working group also applied their peptoid design to build potent ruthenium(II), 154 cobalt(II) 155 , and zinc(II) 156 chelators (Table 2). The Kirshenbaum working group identified peptoid-based nickel(II) chelators with the help of bench-top X-ray fluorescence (XRF, Table 2).…”
Section: Figurementioning
confidence: 99%
“…We targeted Zn II selectivity over other metal ions in the IW series (including Cu II ) and heavy-metal ions, given the diverse structural and functional roles Zn II ions play in natural metalloproteins, , and the vulnerability of natural Zn II coordination sites to deactivation by heavier metal ions ( e.g ., Cd II , Pb II ). Indeed, the design of selective Zn II chelators has been broadly pursued using a variety of molecular and macromolecular platforms such as fluorogenic ligands, , peptoids, and proteins. , We report here the probabilistic design and the structural, biophysical, and biochemical characterization of a reengineered dimeric assembly, B 2 , which displays Zn II selectivity over all other tested metal ions including Cu II . Such selective, anti-IW Zn II binding is achieved thanks to the formation of a unique trinuclear Zn coordination motif consisting of His and Glu residues arranged in a tetrahedral geometry.…”
Section: Introductionmentioning
confidence: 99%
“…[5], [14] Notwithstanding zinc ions are more abundant than copper ions in the synaptic cleft, its redox inertness and the low propensity for Aβ make them less harmful than redox competent Cu ions. [14,15] The need for selectivity between Cu and Zn ions has emerged in the field of the chelation therapy [16,17] and Hureau's group has recently addressed this issue in AD. [18][19][20] In this context, Cu homeostasis is considered a valuable target in AD treatment, [21,22] and the possibility of using metal chelators or ionophores to regenerate metal homeostasis and then inhibit the progressive neurodegeneration is largely studied.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding zinc ions are more abundant than copper ions in the synaptic cleft, its redox inertness and the low propensity for Aβ make them less harmful than redox competent Cu ions [14,15] . The need for selectivity between Cu and Zn ions has emerged in the field of the chelation therapy [16,17] and Hureau's group has recently addressed this issue in AD [18–20] …”
Section: Introductionmentioning
confidence: 99%